Lean Assessment in Selected Electric and Electronics(E&E) Companies in Ipoh, Perak Using SLAT - Teoh Yong Heng; Atan @ Yaakub, Siti Anisah (Research in Management of Technology and Business, 2021)
Lean strategy is very important to manufacturing industry particularly, electric and electronics because it provides concepts, procedures and tools to eliminate wastes from the manufacturing systems. E&E industry nowadays are facing two big challenges which are lack of proper standardization and stick to conventional approach. The purpose of this research is to evaluate lean performance (actual vs target) from nine key areas of manufacturing in selected E&E companies in Ipoh, Perak. Besides, this study also looked for companies that achieve the best lean in each nine areas of manufacturing. Assessment tool used in this study is developed by Quarterman Lee from Strategos Incorporation which known as Strategos Lean Assessment Tool (SLAT). Questionnaire which contains lean assessment questions adopted from SLAT were given to participated companies. There were five E&E companies located in Ipoh, Perak participated in this research. SLAT measures nine important aspect of production process which are inventory, team approach, processes, maintenance, layout and material handling, suppliers, setups, quality, and scheduling and production control. Data from the questionnaire were keyed-in and calculated in SLAT score worksheet in Microsoft Excel and the result of the assessment is in the form of radar chart. The five E&E companies in this research achieved their lean performance in different key areas. The results of this research can help the participated companies to find out the gap between actual performance and the target performance of their lean achievement.